Bioinert ceramics scaffolds for bone tissue engineering by laser-based powder bed fusion: a preliminary review - Kamboj Nikhil; Piili Heidi; Ganvir Ashish; Gopaluni Aditya; Nayak Chinmayee; Moritz Niko; Salminen Antti (United Kingdom, 2025)
The implementation of laser powder bed fusion (PBF-LB) on ceramics is far more demanding than their metallic and polymeric counterparts for bone tissue engineering (BTE). The review will shed light on bioinert ceramics-based biomaterials manufacturing through PBF-LB incorporating alumina and yttria-stabilized zirconia as oxide-based ceramics and nitride-based ceramics as non-oxide-based ceramics with particular prominence on their properties and requirements for biomedical devices and BTE. The review paper will also classify bioinert scaffolds processed through PBF-LB as a medium to manufacture drug delivery systems (DDS) and to ameliorate critical-sized bone defects based on the fracture site length of the bone with the various modes of functionalization through the incorporation of drugs, stem cells, and growth factors for personalized medicine.
NOLAMP- Nordic Laser Materials Processing Conference (19TH-NOLAMP-2023) 22/08/2023 - 24/08/2023 Turku, Finland